NALAR HUKUM PRISMATIK DALAM KONTEKS HUKUM NASIONAL - Akhmad Rudi Maswanto; Ahmad Khoirul Anam (MAQASHID, 2021)
Indonesia's rule of law is a combination of the rechtstaat concept and the rule of law. It can be seen from the side of law enforcement that emphasizes the importance of a just law of certainty and the importance of law efficacy. Other criteria state that Indonesian law isa crystallization of the source of pancasila law and the bill 45,combining the good elements of the concept of individualism and communality/collectivism that are accepted by pancasila, where personal rights are part of a feeling of personal ownership in the "just and lawful humanity" contest. And appreciate the cohesion in every joint of society's life reflected in the "union of Indonesia" scheme that soekarno clarified asa state of community on a principle of cooperation. This characteristic of Indonesia is what distinguishes legal systems from other countries. Hence the term pancasila law. When linked with the combining literature between more than one option at best, it is referred to as a prismatic choice and therefore as a prismatic law.